2021
DOI: 10.3389/fpls.2021.782352
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BBX18 Promotes Thermomorphogenesis Through the PRR5-PIF4 Pathway

Abstract: Thermomorphogenesis is the morphological response of plants to an elevation in the ambient temperature, which is mediated by the bHLH transcription factor PIF4. The evening-expressed clock component, PRR5, directly represses the expression of PIF4 mRNA. Additionally, PRR5 interacts with PIF4 protein and represses its transactivation activity, which in turn suppresses the thermoresponsive growth in the evening. Here, we found that the B-box zinc finger protein, BBX18, interacts with PRR5 through the B-Box2 doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Instead, the ZTL‐PRR5 module might determine the sensitivity of hypocotyl growth to high temperatures by affecting the maximum activity of PIF4. Given that PRR5 is a negative regulator of high temperature‐mediated hypocotyl growth (Hwang et al, 2021; Zhu et al, 2016), the elevation in PRR5 level at high temperatures may play a role in preventing exaggerated high temperature responses, similar to HFR1 (Foreman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the ZTL‐PRR5 module might determine the sensitivity of hypocotyl growth to high temperatures by affecting the maximum activity of PIF4. Given that PRR5 is a negative regulator of high temperature‐mediated hypocotyl growth (Hwang et al, 2021; Zhu et al, 2016), the elevation in PRR5 level at high temperatures may play a role in preventing exaggerated high temperature responses, similar to HFR1 (Foreman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These factors are plant‐specific nuclear proteins that act in the clock genetic circuit and regulate the expression of clock‐output genes. Both TOC1 and PRR5 exhibit transcription repression activity and directly interact with PIF4 to inhibit its transcription activation activity, thereby suppressing PIF4‐mediated growth promotion (Hwang et al, 2021; Zhu et al, 2016). TOC1 and PRR5 also interact with other PIF members, including PIF3 and PIF7, and suppress shade avoidance responses (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has reported that BBX18 and BBX23 interact with ELF3 to positively regulate thermomorphogenesis which dependent on COP1 and PIF4 (Ding et al 2018). In addition, BBX18 interacts with PRR5 to alleviate the PRR5-mediated suppression of PIF4 activity, concomitantly enhancing the thermoresponsive hypocotyl growth in a ELF3 independent pathway (Hwang et al 2021). BBX20, which is transcriptionally repressed by BZR1, promotes photomorphogenesis and represses brassinosteriod signaling pathway (Fan et al 2012).…”
Section: Bbxs Act As Transcriptional Regulatorsmentioning
confidence: 99%
“…Thereby, BBX18 and BBX23 positively regulate thermomophogenic development in a ELF3 dependent manner (Ding et al 2018). However, BBX18 is also documented to associate with PRR5 to alleviate the PRR5-mediated suppression of PIF4 activity which strengths the thermoresponsive hypocotyl growth in a ELF3 independent pathway (Hwang et al 2021). Thus, plants employ BBX18 to adapt to elevated ambient temperature both in ELF3 dependent and independent pathway.…”
Section: Functions Of Bbxs In Abiotic Stress Responsementioning
confidence: 99%
“…However, it is possible to genetically alter soybeans to reduce this photoperiod sensitivity, creating strains that can be grown in a wide range of locations and agricultural settings, to increase yields. Core genes in the light signaling pathway, such as Suppressor of phytochrome A (SPA), Blue light inhibitors of cryptochromes (BIC) and Pseudoresponse regulator 5 (PRR5), sense changes in the light environment, which in turn affects plant growth and development ( Wang et al., 2017 ; Hwang et al., 2021 ; Ponnu and Hoecker, 2021 ). For example, GmBICs regulate soybean stem elongation under low levels of blue light ( Mu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%